Diagnosing ancient Diphyllobothriasis from Chinchorro mummies - Karl Reinhard; Otto Urban (Memorias do Instituto Oswaldo Cruz, 2003)
Diphyllobothrium pacificum has been reported as a human parasite from coprolites and skeletons in Peru and Chile. Our analysis of Chinchorro mummies from Chile provides the oldest evidence of D. pacificum directly associated with human mummies. These mummies date between 4,000 and 5,000 years ago. The basis for our diagnosis is presented. We find that the size of the eggs in the mummies is smaller than other discoveries of D. pacificum. We suggest that this is due to the peculiar circumstances of preservation of parasite eggs within mummies and the release of immature eggs into the intestinal tract as the tapeworms decompose after the death of the host. This information is important to consider when making diagnoses from mummies.